Towards the complete proteinaceous regulome of Acinetobacter baumannii. Issue 3 (23rd March 2017) - Casella, Leila G; Weiss, Andy; Pérez-Rueda, Ernesto; Antonio Ibarra, J; Shaw, Lindsey N
Abstract : The emergence of Acinetobacter baumannii strains, with broad multidrug-resistance phenotypes and novel virulence factors unique to hypervirulent strains, presents a major threat to human health worldwide. Although a number of studies have described virulence-affecting entities for this organism, very few have identified regulatory elements controlling their expression. Previously, our group has documented the global identification and curation of regulatory RNAs in A. baumannii . As such, in the present study, we detail an extension of this work, the performance of an extensive bioinformatic analysis to identify regulatory proteins in the recently annotated genome of the highly virulent AB5075 strain. In so doing, 243 transcription factors, 14 two-component systems (TCSs), 2 orphan response regulators, 1 hybrid TCS and 5 σ factors were found. A comparison of these elements between AB5075 and other clinical isolates, as well as a laboratory strain, led to the identification of several conserved regulatory elements, whilst at the same time uncovering regulators unique to hypervirulent strains. Lastly, by comparing regulatory elements compiled in this study to genes shown to be essential for AB5075 infection, we were able to highlight elements with a specific importance for pathogenic behaviour. Collectively, our work offers a unique insight into the regulatory network of A. baumannii strains, and provides insight into the evolution of hypervirulent lineages.